2019
DOI: 10.1016/j.jceh.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of Hepatocellular Carcinoma: A Review of Literature

Abstract: Approximately 700,000 people die of Hepatocellular Carcinoma (HCC) each year worldwide, making it the third leading cause of cancer related deaths. Rupture is a potentially life-threatening complication of HCC. The incidence of HCC rupture is higher in Asia and Africa than in Europe. In Asia approximately 10% of patients with a diagnosis of HCC die due to rupture each year. Spontaneous rupture is the third most common cause of death due to HCC after tumor progression and liver failure. The diagnosis of rupture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 87 publications
2
128
0
4
Order By: Relevance
“…A number of factors that are independently related to rHCC have been identified by previous studies, further strengthening the confidence with which APAS score might be applied in clinical practice. Consistent associations were shown for PFLS and tumor size of >5 cm [ 2 12 ]. Tumor size has been recognized as an important risk factor for spontaneous rupture, although this may be due to other related variables, such as vascular invasion and tumor grade, rather than the absolute maximum tumor size [ 12 13 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…A number of factors that are independently related to rHCC have been identified by previous studies, further strengthening the confidence with which APAS score might be applied in clinical practice. Consistent associations were shown for PFLS and tumor size of >5 cm [ 2 12 ]. Tumor size has been recognized as an important risk factor for spontaneous rupture, although this may be due to other related variables, such as vascular invasion and tumor grade, rather than the absolute maximum tumor size [ 12 13 ].…”
Section: Discussionsupporting
confidence: 54%
“…HCC patients with PFLS had an increased risk of rHCC, as compared with other tumor locations [ 7 14 ]. These indicated that normal parenchyma surrounding liver cancer can protect tumors from rupture; thus, protruded tumors without surrounding parenchyma may easily rupture due to compression or friction with adjacent organs [ 2 15 ]. Interestingly, ascites remained predictive for rHCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is causing an increasing number of deaths in Australia; the 5‐year survival rate from diagnosis is about 16% . Tumour rupture is a life‐threatening complication and the third most common cause of death (after tumour progression and liver failure) for people with HCC; mortality caused by rupture during the acute phase has been reported to be 25–75% in Asian countries . The poor prognosis is related to intraperitoneal haemorrhage and the potential for intraperitoneal metastases.…”
mentioning
confidence: 99%
“…Hypotheses about the cause of spontaneous rupture include rapid growth and necrosis, splitting of the overlying parenchyma or vessel erosion, increased intratumoral pressure with hepatic vein occlusion, and coagulopathy . Tumour size exceeding 50 mm and superficial location are risk factors for rupture …”
mentioning
confidence: 99%